Characterization of disinfection byproduct formation and associated changes to dissolved organic matter during solar photolysis of free available chlorine. (1st December 2018) - Young, Tessora R.; Li, Wentao; Guo, Alan; Korshin, Gregory V.; Dodd, Michael C.
Abstract: Solar irradiation of chlorine-containing waters enhances inactivation of chlorine-resistant pathogens (e.g., Cryptosporidium oocysts), through in situ formation of ozone, hydroxyl radical, and other reactive species during photolysis of free available chlorine (FAC) at UVB-UVA wavelengths of solar light (290–400 nm). However, corresponding effects on regulated disinfection byproduct (DBP) formation and associated dissolved organic matter (DOM) properties remain unclear. In this work, when compared to dark chlorination, sunlight-driven FAC photolysis over a range of conditions was found to yield higher DBP levels, depletion of DOM chromophores and fluorophores, preferential removal of phenolic groups versus carboxylic acid groups, and degradation of larger humic substances to smaller molecular weight compounds. Control experiments showed that increased DBP levels were not due to direct DOM photolysis and subsequent dark reactions with FAC, but to co-exposure of DOM to FAC and reactive species (e.g., O3, HO, Cl, Cl2 -, ClO ) generated by FAC photolysis. Because solar chlorine photolysis can enable inactivation of chlorine-resistant pathogens at far lower CT FAC values than chlorination alone, the increases in DBP formation inherent to this approach can likely be offset to some extent by the ability to operate at significantly decreased CT FAC . Nonetheless, these findings demonstrate that applications of solar chlorine photolysis will require careful attention to potential impacts on DBP formation. Graphical abstract: Highlights: Solar chlorine photolysis increases THM and HAA formation in DOM-containing waters. DBP formation correlates with extensive photobleaching and decreased MW of DOM. Photogenerated ROS, RHS, and O3 drive DBP precursor generation and destruction. THM and HAA levels can be maintained below MCLs in waters with low DOC and bromide. Use of solar chlorine photolysis for disinfection requires attention to DBP impacts.